HIPOTEZA OSTATECZNEJ DECYZJI. FILOZOFICZNE UJĘCIE KONCEPCJI ŚMIERCI LADISLAUSA BOROSA - Juszkiewicz, Wojciech (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Considering the question of death, Ladislaus Boros presents a hypothesis of final decision. According to him, death opens up a possibility of the first fully personal human act. Therefore death is the existentially privileged place of conscious development, freedom, meeting with Absolute, and making a decision about eternal destiny. Boros examines his assumption from philosophical and theological perspectives. The article focuses on his philosophical approach to the problem. The moment of death is a timeless turn, but its timelessness is a condition of the transition which exists in time. If the turn was not timeless, the two moments – of before and of after – could not overlap each other and create a situation which is comprehensive and exists in time. The starting point for Boros is the basic act of philosophy – surprise. Boros looks for the dimension of death in the internal structure of human life. That structure can be grasped where the split of our existence is revealed. That is why Boros refers to the reflection of those philosophers who most deeply experienced the duality of our existence. Analyzing views of Blondel (the analysis of volition), Marechal (the analysis of cognition), Bergson (the analysis of perception and memory), Marcel (the analysis of love), allows to state that death plays a crucial role in human development. Boros creatively develops their achievemnts and leads to significant consequences. According to Boros, man truly comes into existence only at the moment of his death.